Kinetics of Vanillin and Vanillic Acid Production from Pine Kraft Lignin - Dos Santos, Ricardo Javier (2024)
Vanillin (4-hydroxy-3-methoxybenzaldehyde) is the main component of natural vanilla and a relevant substance in the flavoring and aromatic industries. This study presents a kinetic model to explain both vanillin and vanillic acid concentrations achieved in the alkaline oxidation of pine kraft lignin. Considering that they come from the same precursors, this approach allows an understanding of vanillin production with reaction conditions that minimize the vanillic acid pathway directly from the lignin oligomers, thus maximizing vanillin production. This study involves the effects of oxygen partial pressure, temperature, and the presence or absence of a catalyst (CuSO4 and Fe2 (SO4 )3 mixture) on the vanillin and vanillic acid yields. An adapted reactor (M/K Systems Inc., Williamstown, MA, USA) with a recirculation and spray liquids system was used in the experiments. The experiments were performed using one liter of a solution of NaOH 2 M and 60 g of lignin. During the lignin oxidation reaction, liquid samples were analyzed at different times (from 0 to 200 min). The oxidation products were quantified by liquid chromatography (HPLC). The catalyzed experiments presented higher maximum vanillin yields than the non-catalyzed ones (39.2–39.6% on nitrobenzene oxidation) achieved at 150 ◦C. A kinetic model is proposed where the kinetic parameters were estimated using Monte Carlo methods, fitting satisfactorily to the experimental results. The statistical analysis of the kinetic parameters showed that all the studied variables significantly affect the vanillin yield.